Microbial communities during the composting process of Agaricus subrufescens and their effects on mushroom agronomic and nutritional qualities - Wang, Chunxia; Wang, Dongxia; Li, Chao; Ge, Zhaopeng; Hao, Liubin; Albasher, Gadah; Feng, Fan; Sun, Yue; Lyu, Yanfen; Zheng, Suyue (Frontiers in Microbiology, 2024)
Tunnel composting technology for preparing Agaricus subrufescens cultivation media can achieve a higher biological efficiency (BE) and a lower contamination rate (CR). However, this technology lacks in-depth and systematic study. In the present study, the changes in the microbiome and microbial metabolic functions were surveyed using metagenomic analysis. The physicochemical parameters, agronomic properties and nutritional qualities were also evaluated. Results showed that the contents of cellulose, hemicellulose and lignin dropped to 10.18%, 11.58%, 27.53%, respectively at the end of composting. The tunnel composting technology led to significant increases in crude protein content (32.56%) and crude fiber content (13.68%). Variations of physicochemical characteristics led to different successions of microbial communities. Bacteria manifested significantly higher abundance than fungi. Firmicutes, Actinobacteriota, Chloroffexi and Deinococcota were the predominant bacterial phyla. Ascomycota and Basidiomycota were the dominant fungal phyla in the thermophilic phase. Pseudonocardia, Truepera and Thermopolyspora were positively correlated with the yield of A. subrufescens. In addition to TN, most of the physicochemical properties were significantly correlated with fungal communities in the thermophilic phase. The metabolisms of carbohydrate, amino acid and energy were the primary enrichment pathways. These findings deepen the understanding of microbial communities composition during the composting of A. subrufescens substrates. Moreover, this study provides a basis for improving tunnel composting technology.